Understanding Readmissions in Medicare Beneficiaries During the 90‐Day Follow‐Up Period of an Acute Myocardial Infarction Admission. Issue 21 (5th November 2019) - Culler, Steven D.; Kugelmass, Aaron D.; Cohen, David J.; Reynolds, Matthew R.; Katz, Marc R.; Brown, Phillip P.; Schlosser, Michael L.; Simon, April W.
Abstract : Background: Medicare has a voluntary episodic payment model for Medicare beneficiaries that bundles payment for the index acute myocardial infarction (AMI) hospitalization and all post‐discharge services for a 90‐day follow‐up period. The purpose of this study is to report on the types and frequency of readmissions and identify demographic and clinical factors associated with readmission of Medicare beneficiaries that survived their AMI hospitalization. Methods and Results: This retrospective study used the Inpatient Standard Analytical File for 2014. There were 143 286 Medicare beneficiaries with AMI who were discharged alive from 3619 hospitals. All readmissions occurring in any hospital within 90 days of the index AMI discharge date were identified. Of 143 286 Medicare beneficiaries discharged alive from their index AMI hospitalization, 28% (40 145) experienced at least 1 readmission within 90 days and 8% (11 477) had >1 readmission. Readmission rates were higher among Medicare beneficiaries who did not undergo a percutaneous coronary intervention in their index AMI admission (34%) compared with those that underwent a percutaneous coronary intervention (20.2%). Using all Medicare beneficiary's index AMI, 27 comorbid conditions were significantly associated with the likelihood of a Medicare beneficiary having a readmission during the follow‐up period. The strongest clinical characteristics associated with readmissions were dialysis dependence, type 1 diabetes mellitus, and heart failure. Conclusions: This study provides benchmark information on the types of hospital readmissions Medicare beneficiaries experience during a 90‐day AMI bundle. This paper also suggests that interventions are needed to alleviate the need for readmissions in high‐risk populations, such as, those managed medically and those at risk of heart failure.